A novel 1T2R self-reference physically unclonable function suitable for advanced logic nodes for high security level applications. (1st May 2022) - Lin, Yu-Hsuan; Lee, Dai-Ying; Lee, Ming-Hsiu; Tseng, Po-Hao; Chen, Wei-Chen; Hsieh, Kuang-Yeu; Wang, Keh-Chung; Lu, Chih-Yuan
Abstract: A self-reference resistive random-access memory (ReRAM)-based one-transistor, two-ReRAM (1T2R) physically unclonable function (PUF) is proposed to provide a hardware security feature for electrical products in the IoT/5G era. There are four advantages from the proposed structure: (1) a small cell size; (2) intrinsic randomness; (3) no programming circuit; and (4) no data retention concerns. The conduction mechanism, temperature dependency, and read fluctuation of the pristine ReRAM device are studied. An information–address separation scheme is proposed which not only reduces the impact of the read noise and the temperature effect, but also improves system integrity against hardware attacks. The proposed 1T2R PUF unit also has great potential for use as a random seed for linear-feedback shift registers in pseudo random number generators with high unpredictability, good randomness, and a high data rate.